THE TRADITION OF MEMORIZING THE KORAN IN AN ETHNOMATHEMATICS PERSPECTIVE: A CASE STUDY AT THE RUMAH TAHFIDZ BAITU USYSYAQIL QURAN (RTBUQ) PURWOKERTO - Kusno, Kusno; Nalim, Yusuf; Supiyati, Sri; Setiyaningsih, Eka; Makhful, Makhful (International Journal of Multidisciplinary Research and Literature, 2024)
The tradition of memorizing the Koran at the Rumah Tahfidz Baitu Usysyaqil Quran (RT BUQ) Banyumas Regency, Central Java, Indonesia, contains various applications of mathematics but is not widely known from a mathematics learning perspective. This research aims to reveal the phenomenon of applying mathematics to the tradition of memorizing the Koran at RT BUQ as an innovation in contextual mathematics learning based on local culture and with Islamic nuances. This ethnographic research is at RTBUQ Banyumas Regency, Central Java, Indonesia. The subjects in this research were Muhammad Husna (R-1) and Sur'ati Istiqomah (R-2), RTBUQ supervisors, and Muhammad Azka (R-3), RTBUQ students. Data collection uses in-depth interview techniques, observation, field notes and documentation. Data were analyzed using the results of interpretation and translation of phenomena found based on the informant's conception of the meaning and original language of the informant with the researcher's language after in-depth understanding through focus group discussions (FGD). The research results show that the tradition of memorizing the Koran at RTBUQ involves using sets, number patterns, sequences and arithmetic series. The findings of this research can be recommended to strengthen mathematics learning based on local wisdom and Islamic nuances